The HRs entrepreneurial competency development and the effects on the performance of small and medium enterprises in South Sulawesi - Saban Echdar (Universitas Hayam Wuruk Perbanas, 2014)
Small and Medium Enterprises (SMEs) can expand employment and provide economic contribution to economic development, and increase public incomes as well as boost economic growth. Thus, they play a role in achieving national economic stability. However, the quality of human resources in SMEs still low, as well as advanced production techniques, low innovation, and lower banking access. This study aimed to analyze the influence of the knowledge, skills, and abilities of entrepreneurship of human resource of SMEs towards the performance of SMEs in South Sulawesi. The population study was all SMEs in South Sulawesi by clustering at four cities: Makassar, Pare-Pare, Takalar, and Bulukumba totaled 680,610 business units with 3,403,150 workers. The purposive sampling and random sampling of 160 respondents was employed and the analysis was by using multiple linear regressions. It shows that knowledge of entrepreneurship has positive but not significant influence towards the performance of SMEs. Entrepreneurial Skills and competence both have positive and significant influence towards the performance of SMEs because they were able to manage the business, although not evenly. Entrepreneurship ability more dominantly affects the performance of SMEs due to the volume of business or sales began to increase, with net profit rising.